Digital Book on Motor Development in Sports Education at Sriwijaya University - Asrul, Muhammad; Hartati, Hartati; Aryanti, Silvi (Universitas Negeri Semarang, 2023)
This research aims to produce a Digital-Based Teaching Book on Motor Growth and Development in the Sports Education Program at FKIP Unsri. The method used is Research and Development (RD), which aims to create a digital-based teaching book on motor growth and development. Sampling involved Physical Education students who had taken motor development courses. Data collection methods included validity tests, practicality tests, and effectiveness tests. Research instruments included validation sheets, questionnaires, and student learning outcome tests. Data analysis techniques involved validity, practicality, and effectiveness analysis. The findings revealed the book's high validity, as indicated by the research validator's results, with an average score of 4.27, classifying it as highly valid. According to student responses in the questionnaire, the book was considered highly practical, achieving a practicality score of 3.55, classified as very positive. Additionally, the student learning outcome test showed the digital-based teaching book on motor growth and development in the Sports Education Program at FKIP Unsri to be effective, with a high proficiency rate of 96.4%. In conclusion, this research confirms that the digital-based teaching book on motor growth and development in the Sports Education Program at FKIP Unsri is highly valid, practical, and effective for supporting learning activities, meeting high standards.